2016
DOI: 10.1051/0004-6361/201527065
|View full text |Cite
|
Sign up to set email alerts
|

MUSE crowded field 3D spectroscopy of over 12 000 stars in the globular cluster NGC 6397

Abstract: We present a detailed analysis of the kinematics of the Galactic globular cluster NGC 6397 based on more than ∼18 000 spectra obtained with the novel integral field spectrograph MUSE. While NGC 6397 is often considered a core collapse cluster, our analysis suggests a flattening of the surface brightness profile at the smallest radii. Although it is among the nearest globular clusters, the low velocity dispersion of NGC 6397 of <5 km s −1 imposes heavy demands on the quality of the kinematical data. We show tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 79 publications
7
90
0
Order By: Relevance
“…Recently, Kamann et al (2016) used integral field spectroscopic data and suggested that the surface brightness profile and velocity dispersion profile could either be explained by the presence of an intermediate-mass black hole with a mass of 600 M ⊙ -which agrees with an earlier suggestion by de Rijcke et al (2006) of ≈ 1300 to 400M ⊙ , based on radio continuum emission -or with a dark stellar component.…”
supporting
confidence: 78%
“…Recently, Kamann et al (2016) used integral field spectroscopic data and suggested that the surface brightness profile and velocity dispersion profile could either be explained by the presence of an intermediate-mass black hole with a mass of 600 M ⊙ -which agrees with an earlier suggestion by de Rijcke et al (2006) of ≈ 1300 to 400M ⊙ , based on radio continuum emission -or with a dark stellar component.…”
supporting
confidence: 78%
“…To reliably separate physical radial velocity variations from those caused by the finite accuracy of our measurements, a proper knowledge of the measurement uncertainties is key. We calibrated the uncertainties from the observed epoch-to-epoch variations in a similar manner to Kamann et al (2016). It is based on the idea that (in the absence of physical variations due to binary or variable stars) the normalised velocity offsets,…”
Section: Full-spectrum Fittingmentioning
confidence: 99%
“…Calibrated uncertainties are obtained by multiplying the original uncertainties with the actual standard deviation of the δv los distribution. In contrast to Kamann et al (2016), where the calibration was performed by grouping stars with extracted spectra of comparable S/N, we grouped the stars according to their T eff , log g, and M/H measurements. For each star, we inferred the correction factor for the formal uncertainties of its radial velocity measurements based on the distribution of the δv los values of the 100 closest stars in this threedimensional space.…”
Section: Full-spectrum Fittingmentioning
confidence: 99%
“…Indeed, radial velocities have been obtained essentially only for the brightest stars, giants and subgiants, which have very similar masses. To date, the measure of a significant number of radial velocities for stars in a range of masses has been performed through integral field spectroscopy only in the GC NGC 6397, leading however to uncertain results (Kamann et al 2016). The same kind of analysis made through proper motions requires superb astrometric accuracies that have been achieved only recently using Hubble Space Telescope (HST) multi-epoch observations providing evidence for mass-dependent kinetic temperature in M15 (Bellini et al 2014).…”
Section: Introductionmentioning
confidence: 99%